2008
DOI: 10.5253/078.096.0105
|View full text |Cite
|
Sign up to set email alerts
|

Differential Development of Breeding Plumage in Adult and Second-Year Male RuffsPhilomachus pugnax

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…According to van Rhijn (1991) only a small proportion of males and females will reproduce when one year old. First year male ruffs refuel less rapidly (Karlionova et al 2008) and develop less elaborated nuptial plumage than adults, behave mostly as marginal males and are less involved in displays at leks and have lower mating chances (van Rhijn 1991). We thus considered age as an additive effect.…”
Section: Statistical Modellingmentioning
confidence: 99%
“…According to van Rhijn (1991) only a small proportion of males and females will reproduce when one year old. First year male ruffs refuel less rapidly (Karlionova et al 2008) and develop less elaborated nuptial plumage than adults, behave mostly as marginal males and are less involved in displays at leks and have lower mating chances (van Rhijn 1991). We thus considered age as an additive effect.…”
Section: Statistical Modellingmentioning
confidence: 99%
“…Sexing was based on wing length (Prater et al 1977;Jukema and Piersma 2006). Age was determined on the basis of leg colour (orange for adults, greenish for first-year birds), the presence or absence of juvenile inner median coverts (Prater et al 1977), and also by examining breeding plumage development (Meissner and Scebba 2005;Karlionova et al 2008). For stable isotope analyses, we collected feather material for all birds captured and blood for 173 of them (163 males and 10 females), which were then used for stable isotope analysis.…”
Section: Field Methodsmentioning
confidence: 99%
“…In March-April large numbers aggregate in a few areas, usually in open landscapes with shallow water and short-sward grasslands, e.g. the grasslands in Friesland in The Netherlands (Wymenga 1999, Jukema et al 2001a), the Seewinkel area in Austria (Laber 2003), the Sivash mudflats and lagoons in Ukraine (Chernichko et al 1991), Hortobagy in Hungary (Kube et al 1998) and the Pripyat Valley in Belarus (Karlionova et al 2008). A study addressing the migratory connection between a wintering area, the Senegal Delta, and staging areas in Europe concluded that during northward migration the Senegalese winterers typically moved through the UK and The Netherlands (OAG Münster 1989a).…”
mentioning
confidence: 99%